Greedily assemble tandem repeats for next generation sequences. (8th November 2019) - Jiang, Yongqing; Lu, Jinhua; Hou, Jingyu; Zhou, Wanlei
Eukaryotic genomes contain high volumes of intronic and intergenic regions in which repetitive sequences are abundant. These repetitive sequences represent challenges in genomic assignment of short read sequences generated through next generation sequencing and are often excluded in analysis losing invaluable genomic information. Here we present a method, known as tandem repeat assembler (TRA), for the assembly of repetitive sequences by constructing contigs directly from paired-end reads. Using an experimentally acquired data set for human chromosome 14, tandem repeats >200 bp were assembled. Alignment of the contigs to the human genome reference (GRCh38) revealed that 84.3% of tandem repetitive regions were correctly covered. For tandem repeats, this method outperformed state-of-the-art assemblers by generating correct N50 of contigs up to 512 bp.